(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Customer retention is the ability of a business to transform one-time clients into patron customers and keep them from switching to a rival. Employee-customer interaction is a connection formed between the employee and the customer in a food establishment. Employee-customer interaction affects a business’s customer retention. The result of this study shows that the majority of the respondents are female in the age group of 19 to 30 years old, with a percentage of 56%. It implies that adults want food that is tasty, and elders are more conscious of their health than adults. The results of this study show that the problem encountered by employees in having customer retention was food quality; this means that most of the respondents are satisfied with the taste and flavor of the food, and it affects the satisfaction of the customers. The respondents assess the effects of employee- customer interaction in terms of customer complaints when the employees offer solutions to the problems; this means that discussing solutions helps businesses provide good customer service. This study recommends the company continue to serve food that is flavorful and tasty and conduct product development to satisfy customers and increase sales. The employees should practice more in handling customer complaints as it will help the business provide great customer service and retain customers.